Use of CentriMag for refractory cardiogenic shock in a puerperal woman: case report - Pêgo-Fernandes, Paulo Manuel (2021)
CONTEXT: Heart failure in Brazil is a major public health problem and, even with advances in treatment, it still presents high morbidity and mortality. As a treatment option, mechanical circulatory assist devices (MCADs) have greatly increased in importance over the last decade. CASE REPORT: This report concerns a case of refractory cardiogenic shock due to acute myocarditis in a 35-year-old puerperal female patient who presented with retrosternal pain, fatigue and dyspnea. At the hospital, she was diagnosed with myocarditis. There was no improvement in perfusion even after receiving dobutamine, intra-aortic balloon passage (IAB) and venoarterial extracorporeal membrane oxygenation (VA-ECMO). Therefore, it was decided to implant a MCAD (CentriMag). During hospitalization, recovery from the bi-ventricular dysfunction was achieved. The CentriMag device was removed 10 days after it had been implanted, and the patient was discharged after another 8 days. The myocarditis was proven to be due to the Coxsackie virus. CONCLUSIONS: The decision to implant a MCAD should be individualized, as patient profiles do not always match the indications in the guidelines and protocols. In this study, clinical discussion of the case among the medical and multi-professional teams was essential in order to be able to successfully reverse the patient’s severe clinical condition without sequelae, through using a CentriMag implant.